2022
DOI: 10.3389/fmed.2022.842121
|View full text |Cite
|
Sign up to set email alerts
|

Changes in HIV Testing Utilization Among Chinese Men Who Have Sex With Men During the COVID-19 Pandemic in Shenzhen, China: An Observational Prospective Cohort Study

Abstract: BackgroundThe Coronavirus Diseases 2019 (COVID-19) directly affects HIV prevention and sexual health services utilization among men who have sex with men (MSM). This study investigated changes in human immunodeficiency virus (HIV) testing utilization among MSM before and after the COVID-19 pandemic received initial control in Shenzhen, China.MethodsThis study was a sub-analysis of a prospective observational cohort study conducted among MSM in Shenzhen, China between August 2020 and May 2021. Participants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 50 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…A possible reason for this rise in prevalence may be related to the changes in the COVID-19 pandemic and related control measures over time. Studies have shown that high-risk sexual behaviors among MS decreased during the COVID-19 pandemic due to strict lockdown and social isolation measures, and then rebounded to the level before the COVID-19 outbreak after the pandemic received initial control in China [48]. The prevalence of multiple sexual partners in our study was consistent with that of previous studies.…”
Section: Principal Findingssupporting
confidence: 89%
“…A possible reason for this rise in prevalence may be related to the changes in the COVID-19 pandemic and related control measures over time. Studies have shown that high-risk sexual behaviors among MS decreased during the COVID-19 pandemic due to strict lockdown and social isolation measures, and then rebounded to the level before the COVID-19 outbreak after the pandemic received initial control in China [48]. The prevalence of multiple sexual partners in our study was consistent with that of previous studies.…”
Section: Principal Findingssupporting
confidence: 89%
“…The findings suggest that positive attitudes toward vaccination and frequent discussions about vaccinations with family and friends can influence individuals’ own attitudes toward vaccination, increasing the likelihood of getting vaccinated ( 44 ). Previous research has indicated that MSM may place importance on the viewpoints of their male sexual partners or peers ( 45 ). Therefore, it can be inferred that they are more likely to be willing to receive vaccinations when their friends or sexual partners are vaccinated, as it provides them with a sense of belonging.…”
Section: Discussionmentioning
confidence: 99%
“…This preference can be attributed to their perception of being at a high risk of MPX infection, which increases their inclination toward vaccination as a preventive measure. Furthermore, social norms and peer influence may also impact vaccine decision-making ( 45 , 56 ). Therefore, it is imperative to provide monkeypox or smallpox vaccinations to MSM who are at a higher risk of monkeypox exposure in order to aid in controlling the recent outbreak of the virus.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous data, about 60% of MSM in Hong Kong received any type of HIV testing in the past six months [ 18 , 23 ]. Given the negative impact of COVID-19 on HIV testing utilization [ 12 , 27 ], we estimated that 45% of local MSM would take up HIV testing within six months during the pandemic [ 10 , 12 ]. A sample size of 280 participants per group would allow us to detect a minimum between-group difference of 12% in this primary outcome (α = 0.05, power = 0.80, two-sided test; PASS 11.0, NCSS LLC).…”
Section: Methodsmentioning
confidence: 99%